Elephants - Michael R. Kremer; Charles Morcom (Fondazione Eni Enrico Mattei (FEEM), 1997)
Existing models of open-access resources are applicable to non-storable resources, such as fish. Many open-access resources, however, are used to produce storable goods. Elephants, rhinos, and tigers are three prominent examples. Anticipated future scarcity of these resources will increase current prices, and current poaching. This implies that, for given initial conditions, there may be rational expectations equilibria leading both to extinction and to survival. Governments may be able to eliminate extinction equilibria by promising to implement tough anti-poaching measures if the population falls below a threshold. Alternatively, they, or private agents, may be able to eliminate extinction equilibria by accumulating a sufficient stockpile of the storable good.
Keywords: D90; Q20; Q22; 330; Storability; Durability; Open-access; Elephants; Fishery; Resources; Multiple equilibria; Rational expectations